Sputtered polycrystalline MgZnO/Al reflective electrodes for enhanced light emission in AlGaN-based homojunction tunnel junction DUV-LED. (1st April 2022) - Matsubara, Taichi; Nagata, Kengo; Kushimoto, Maki; Tomai, Shigekazu; Katsumata, Satoshi; Honda, Yoshio; Amano, Hiroshi
Abstract: In this study, we enhanced the emission power of AlGaN-based tunnel junction deep-ultraviolet LEDs (TJ LEDs) by using a MgZnO and aluminum stacked structure as UV reflective electrodes on the anode side. The emission wavelength of the fabricated TJ LED was 284 nm, and the emission power was 57.3 mW at 63 A cm −2 . The polycrystalline MgZnO enabled both conductivity and UV transmittance to be achieved, approximately doubling with a reflectance of the fabricated TJ LED at 284 nm compared to conventional TJ LED with Ti/Al. These factors contributed to the increased emission power of TJ LEDs.